A instituição da reserva legal na propriedade rural e o conflito entre os princípios da propriedade privada e a função socioambiental - Hoenisch, Emanuele (2016)
The new Forest Code brings expressed the imposition of the maintenance - or even rebuilding - the original vegetation cover, with a view to compliance with the provisions for the purpose of legal reserve, created in order to preserve biodiversity and how efetivador through the social function of property. Such imposition is a translation of the article 225 of the Federal Constitution, which adds that it is all right to a Healthy and balanced environment. The Legal Reserve mind limitation of rural private property, which led to negative impacts, since it is treated as idle area, resulting in financial losses to the owners. Still, it is challenging the constitutionality of this imposing legal reserve, having to justify such questioning the fact attributed to landowners the duty to preserve nature, where the constitutional law provides that it is the duty of the government and of the entire community, not fitting to a small group represented by landowners. Given this limitation of the property by the Legal Reserve, the question arises: is there a conflict between the constitutional principles of private property and environmental function? In the center of this discussion, highlights the issue concerning the objectives of the institute, namely, the need for preservation / restoration of these areas with "forests" or "native vegetation" in order to preserve biodiversity, which is essential for maintenance a balanced environment, the right of present and future generations, as constitutional law. The methodology follows the hypothetical-deductive method, which appears consistent with the proposed work, for the desired conclusion is reached from the assumptions presented, starting from the constitutional provisions and analyzing directly to infra-constitutional legislation. The communication from different areas of knowledge such as law and sustainability are applied to resolve issues. It is observed that in the discussion of the establishment of the Legal Reserve as a generator of conflict between constitutional principles, it is necessary to evaluate the ecological setting (environmental issues) in order to enable the construction of strategies to prevent and combat the causes that led to this administrative limitation of the property. The proposal, therefore, is to analyze the Institute of Legal Reserve in the perspective of socio-biodiversity. It is therefore crucial that the discussion is in a multidimensional way, passing by various systems such as economic, legal, political, social and cultural, which intertwine with environmental issues. Thus, considering that the issue be seamlessly (interdisciplinary), in facing up to challenges, with the filing of appropriate (and effective) solutions, and the urgent protection of the environment.